ANALISIS KESALAHAN PENGGUNAAN BENTUK PERNYATAAN SARAN ~Houga ii dan ~Tara ii PADA MAHASISWA ANGKATAN 2019 PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Wahyudi, M. Ridho; Aibonotika, Arza; Suri, Intan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research is a study of the analysis of student errors on the form and use of ~houga ii and ~tara ii suggestions for students of class 2019 Japanese Language Education Study Program, FKIP, Riau University. The purpose of this study was to analyze student errors and to find out the factors causing student errors in the form and use suggestions of ~houga ii and ~tara ii in Japanese sentences. In this study, a quantitative descriptive method was used using a test instrument consisting of word form indicators and usage and meaning indicators to find out errors and factors causing student errors. Based on the results of tests that have been carried out on 30 students, the average score is 50.36 which is grouped less, while the percentage of student errors as a whole is 49.22%. Of the 30 students, there were 18 students who were in the category of scores below sufficient, this shows that there are still many students who do not understand the statements from the suggestions of ~houga ii and ~tara ii in Japanese sentences. Then, when viewed from the indicators of the questions tested, students are more likely to make mistakes on the word form indicators compared to indicators of use and meaning.Key Words: Error Analysis, ~Houga ii, ~Tara ii.